Progression of Tubulointerstitial Fibrosis and the Chronic Kidney Disease Phenotype - Role of Risk Factors and Epigenetics - Timothy D. Hewitson; Timothy D. Hewitson; Stephen G. Holt; Stephen G. Holt; Edward R. Smith; Edward R. Smith (Frontiers Media S.A., 2017)
Although the kidney has capacity to repair after mild injury, ongoing or severe damage results in scarring (fibrosis) and an associated progressive loss of kidney function. However, despite its universal significance, evidence highlights a population based heterogeneity in the trajectory of chronic kidney disease (CKD) in these patients. To explain the heterogeneity of the CKD phenotype requires an understanding of the relevant risk factors for fibrosis. These factors include both the extrinsic nature of injury, and intrinsic factors such as age, gender, genetics, and perpetual activation of fibroblasts through priming. In many cases an additional level of regulation is provided by epigenetic mechanisms which integrate the various pro-fibrotic and anti-fibrotic triggers in fibrogenesis. In this review we therefore examine the various molecular and structural changes of fibrosis, and how they are influenced by extrinsic and intrinsic factors. Our aim is to provide a unifying hypothesis to help explain the transition from acute to CKD.